THE ROLE OF THE TUTOR IN STUDENT DEVELOPMENT - Amonova, Guli (INTERNATIONAL CONFERENCES, 2023)
The article discusses the role of a tutor in the university. According to the author, the position of a tutor is designed to enrich the educational space of the organization of higher education. In higher education system, a separate person (tutor) appears who is responsible for determining and choosing the individual trajectory of the student at the request of the student himself or in the interests of his family. The article also discusses the differences between a tutor and a curator.